Clinical significance of dispersion imaging by shear wave elastography in the treatment and diagnosis of pancreatic cancer. Issue 4 (24th February 2023) - Takishin, Yunosuke; Kuwatani, Masaki; Nishida, Mutsumi; Mitsuhashi, Tomoko; Kishi, Kazuma; Nagai, Kosuke; Furukawa, Ryutaro; Hirata, Hajime; Hirata, Koji; Kato, Shin; Kawakubo, Kazumichi; Sakamoto, Naoya
Abstract: Background and Aim: Recently, dispersion imaging by shear wave elastography has been developed to visualize a tissue viscosity‐related factor by measuring the dispersion slope. However, clinical significance of dispersion imaging in the field of pancreatic cancer is unknown. This study aimed to investigate the clinical significance of dispersion imaging in the treatment and diagnosis of pancreatic cancer. Methods: We measured shear wave dispersion slope (SWD) (m/s/kHz) and shear wave elasticity (SWE) (kPa) in patients with pancreatic ductal adenocarcinoma (PDA). The primary endpoint was the relationship between the changes in SWD and SWE values before and after chemotherapy and the response to chemotherapy. Secondary endpoints included SWD and SWE values in relation to differences between PDA and non‐PDA sites and histopathological scores of stroma, inflammation, fibrosis, and necrosis in endoscopic ultrasound‐guided fine‐needle aspiration specimens. Results: Fifty‐six patients were included, 30 of whom underwent chemotherapy. There was no relationship between the changes of SWD and SWE values and chemotherapy responses. In 56 patients, the median SWD value was 12.20 m/s/kHz (interquartile range [IQR]: 10.88–13.61) at PDA sites and 13.57 m/s/kHz (IQR: 12.28–16.20) at non‐PDA sites ( P = 0.005). The median SWE value was 8.18 kPa (IQR: 7.00–9.74) at PDA sites and 6.14 kPa (IQR: 5.40–6.77) at non‐PDA sites ( P < 0.001). Histopathological evaluation revealed that inflammation scores were correlated with SWD values ( r s = 0.42, P < 0.001). Conclusions: Dispersion imaging in pancreatic cancer would be useful for diagnosis and assessing inflammation.